Advancing Economic Potential and Stakeholder Engagement on Aceh Singkil Regency - Muhammad Izzudin; Rizwan Achmad (Universitas Pendidikan Ganesha, 2022)
Aceh Singkil Regency's primary objective is to grow the local economy, concentrating on superior goods or industries. Singkil Aceh Administratively, it is located far from the capital city of Nangroe Aceh Darussalam (NAD) Province, which contributes to the region's isolation and underdevelopment. The study examined the economic prospects for accelerated development in Aceh Singkil. Firstly, this study used location quotation (LQ) analysis to establish the leading sector. Secondly, the SWOT analysis used a focus group discussion (FGD). Thirdly, the analysis of stakeholder categories used Grimble and Wellard's theory. The findings showed that agriculture, forestry, and fishery continued to be the primary emphasis of local economic growth of the Aceh Singkil community, and the stakeholders belonging to the dominant category of local economic determinants include the local governments, legislatures, and banks. The dominance of the agriculture, forestry, and fishery sectors is inseparable from the geographical location of Aceh Singkil, a coastal area with a fluvial morphology that allows the three sectors to become the foundation of the community's economy. This research implies that with the existence of three stakeholder dominations, namely local government, legislature, and banking, it is necessary to increase the role of the community, such as farmer groups, planters, and fishermen, in initiating welfare improvement programs independently to support the acceleration of the local economy.